The European Society for Medical Oncology (ESMO) Precision Medicine Glossary. (13th November 2017) - Yates, L R; Seoane, J; Le Tourneau, C; Siu, L L; Marais, R; Michiels, S; Soria, J C; Campbell, P; Normanno, N; Scarpa, A; Reis-Filho, J S; Rodon, J; et al.
Abstract: Background: Precision medicine is rapidly evolving within the field of oncology and has brought many new concepts and terminologies that are often poorly defined when first introduced, which may subsequently lead to miscommunication within the oncology community. The European Society for Medical Oncology (ESMO) recognises these challenges and is committed to support the adoption of precision medicine in oncology. To add clarity to the language used by oncologists and basic scientists within the context of precision medicine, the ESMO Translational Research and Personalised Medicine Working Group has developed a standardised glossary of relevant terms. Materials and methods: Relevant terms for inclusion in the glossary were identified via an ESMO member survey conducted in Autumn 2016, and by the ESMO Translational Research and Personalised Medicine Working Group members. Each term was defined by experts in the field, discussed and, if necessary, modified by the Working Group before reaching consensus approval. A literature search was carried out to determine which of the terms, 'precision medicine' and 'personalised medicine', is most appropriate to describe this field. Results: A total of 43 terms are included in the glossary, grouped into five main themes—(i) mechanisms of decision, (ii) characteristics of molecular alterations, (iii) tumour characteristics, (iv) clinical trials and statistics and (v) new research tools. The glossary classes 'precision medicine' or 'personalised medicine' as technically interchangeable but the term 'precision medicine' is favoured as it more accurately reflects the highly precise nature of new technologies that permit base pair resolution dissection of cancer genomes and is less likely to be misinterpreted. Conclusions: The ESMO Precision Medicine Glossary provides a resource to facilitate consistent communication in this field by clarifying and raising awareness of the language employed in cancer research and oncology practice. The glossary will be a dynamic entity, undergoing expansion and refinement over the coming years.